Design and development of a test rig for hydraulic regenerative braking system / Norhirni Md Zahir - Norhirni , Md Zahir (2012)
In the effort to reduce the consumption of fossils fuels and consequently the release of greenhouse gasses into the atmosphere, there has been a growing interest in the automotive industry to develop and produce hybrid vehicles. Most of the attention on hybrid vehicles nowadays has been on electrical-based hybrids. However, the implementation of electrical-based hybrids on large, heavy vehicles is impractical, due to the size and cost of the batteries required. Additionally, the amount of energy that has to be regenerated for a large vehicle is also huge and this is unsuitable for electrical based systems, which has lower rate of energy transfer. Therefore application of hybrid technology for large vehicles using hydraulic systems has received recent attention. Hydraulic regenerative braking system (HRBS) is a system that reduces the vehicle speed by converting its kinetic energy into potential energy using axial piston pump, and storing it inside a hydro-pneumatic accumulator for future use. When the vehicle accelerates, pressurized working fluid discharges from the accumulator, which in turn converts the stored potential energy into kinetic energy by rotating the driveshaft, thus moving the vehicle. This project is about using a test rig system to investigate the actual behavior of the newly designed HRBS. Concept selection has been conducted to select the most suitable components for the HRBS. Structural analysis by calculation and Finite Element Analysis (FEA) of the test rig chassis and some other parts is done by ABAQUS software. The test rig system is assembled and a simple controller is developed and integrates with the test rig to test the function of the test rig system. This study will have some limitation due to the situation where the chassis is existing from previous research and some of the parts are only an imitation of an actual 5-ton lorry condition during cycle test. The result shows that the system is able to capture and release energy during operation which is an important characteristic in HRBS. It is also discovered that, the smaller the swash plate angle (plate inside axial piston pump), the longer the flywheel spins and the more pressure supplied from the accumulator to the system, the faster the flywheel can spin. With the result of this work, further installation of HRBS system onto an actual 5-ton lorry can be planned.